DETERMINANTS OF POVERTY IN PAPUA PROVINCE: A PANEL DATA REGRESSION APPROACH (2021–2023) - Indrasari, Nurvida; Yulianto, Safa'at (LPPM Universitas Negeri Jakarta, 2025)
Papua Province, as one of the most underdeveloped regions in Indonesia, faces the problem of chronic poverty that occurs continuously. The high percentage of poverty and the low index in the aspects of shaping human development make the analysis of the factors that cause poverty urgent and worth researching. The purpose of this study is to identify the variables that affect the poverty rate in Papua Province in 2021-2023 comprehensively and systematically to identify vulnerable factors so that they can be used as a reference for mapping poverty alleviation policies that are more effective. The method used in this study is panel data regression, considering its advantages in providing a larger amount of data so that it can provide greater information that is not only produced by cross-sectional or time series data only. The data used is a publication from Badan Pusat Statistik (BPS) for 2021-2023 with the number of poor people, average length of schooling, labor force participation rate, per capita expenditure, life expectancy, human development index, gross regional domestic product, and length of schooling as predictor variables. The approach with fixed random effect was chosen to be the most suitable model. According to the results obtained from this analysis, the factor that has a significant effect on the condition of economic insufficiency in Papua Province in 2021-2023 is the number of poor people. These findings emphasize the importance of affirming that poverty alleviation policies need to be focused on reducing the number of poor people through programs that target increasing income and access to basic needs of the community.